Effect of Abelmoschus esculentus Fruit Hydroalcoholic Extract on Pituitary-Testes Axis Hormones and Arginase II Gene Expression in Streptozotocin-Induced Diabetic Adult Rats - Mahya Hosseinpur; Mehrdad Shariati; Ebrahim Hosseini (Fasa University of Medical Sciences, 2020)
Background & Objectives: Diabetes is the most common metabolic disorder that disrupts the reproductive system. This study aimed to investigate the effect of Abelmoschus esculentus fruit hydroalcoholic extract on pituitary-testicular hormones and the expression of Arginase II gene in streptozotocin-induced diabetic adult rats. Material & Methods: In this experimental study, 36 adult Wistar rats were randomly divided into six groups including the control (untreated), positive control (60 mg/kg streptozotocin), negative control (400 mg/kg Abelmoschus esculentus hydroalcoholic extract), experimental 1, 2 and 3 (first 60 mg/kg streptozotocin and then 100, 200 and 400 mg/kg of Abelmoschus esculentus hydroalcoholic extract, respectively). 28 days later, luteinizing hormone (LH), follicle-stimulating hormone (FSH) and testosterone hormones were measured by ELISA and the Arginase II gene expression was measured by Real-Time PCR. The results were analyzed by one-way analysis of variance and Tukey's post hoc tests. Results: Compared to the control group, the levels of FSH and LH hormones increased significantly and the testosterone level decreased significantly in the positive control group. However, there were no significant changes in hormone levels in the negative control group. In experimental groups, the improvement in FSH, LH and testosterone levels was observed as dose-dependent compared to the control group. The expression level of Arginase II gene in the positive control and experimental 1 groups significantly reduced compared to the control group, but no significant changes were observed in the other groups. Conclusion: The Abelmoschus esculentus fruit hydroalcoholic extract in maximum dose has protective effects on the level of pituitary-testicular hormones and the expression of Arginase II gene in diabetic rats.